Pengaruh Capital Adequacy Ratio Dan Return On Asset Terhadap Penyaluran Kredit Pada Bank Umum Yang Terdaftar Dibursa Efek Indonesia Tahun 2013-2019 - Endah Sri Amsiah; Suparno Suparno; H. Ahmad Nawawi (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The purpose of this study was to determine, test and analyze the Influence of the Capital Adequacy Ratio and Return On Assets together on lending to conventional commercial banks.The population taken in this study were public banks listed on the Indonesia Stock Exchange and the sample used was purposive sampling technique with specified criteria. There were 6 banks that publish annual financial reports (annual reports) for the years 2013 – 2019. The research method used is descriptive verification research method sourced from bank financial report data and literature studies. The data obtained were analyzed using classical assumption test analysis, multiple linear regression and hypothesis testing using f test and t test with a significance level of 5%. The results of the partial hypothesis test show that there is an effect of the Capital Adequacy Ratio on Credit Distribution. There is an effect of Return on Assets (ROA) on Credit Distribution. There is an effect of Capital Adequacy Ratio and Return On Assets simultaneously or jointly affecting Credit Distribution. Keywords: Capital Adequacy Ratio and Return On Asset